O PMDB e a sua manutenção no centro do jogo político: de catch all a cartel - Paulo Victor Teixeira Pereira de Melo (2013)
Political parties are central institutions for democracies. Hence, one cannot analyze contemporary democracies without a comprehensive understanding of the role played by parties. They have proven to be the most adaptative entities whiten democratic systems in modern history, capable to adjust themselves to different sets of social, political, institutional and governative structures. This study examines one of the most well succeeded parties in the Brazilian political system: the Party of the Brazilian Democratic Movement (PMDB). It is one of the biggest parties in Brazil and it controls several municipalities, seats in both National Congress and State Assemblies, as well as key places in state governments. It also possesses one of the most robust political machines in the Country. Regardless of it's vast capillarity, PMDB has hardly presented a candidate to the Brazilian Presidency. Still, it always retains central positions on national government coalitions since it helps to maintain high levels of government support on the legislative, being therefore an important figure on Brazilian "coalition presidentialism". This work discusses which party model, among those formulated by the classical literature on parties, best applies to the case of PMDB. Additionally it will analyse the links between party members and it's supporters.